Penguatan Usaha Ekonomi Produktif, Kelompok Swadaya Masyarakat (KSM) Bandeng - Ngurah Pandji Pandji; Imang Dapit Pamungkas; Ririh Dian Pratiwi (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Empowerment in the community must involve all parties, and in their involvement, they are asked to provide the best for the community. On the other hand, the community is asked to be able to follow the directions and instructions as given by the Empowerment, so that in the end the expected results can be obtained. The empowerment this time aims to provide economic strengthening for the Bandeng Non-Governmental Organization (KSM) in Rejomulyo Village, Semarang. Activities include determining the production plan, which is felt to be the most appropriate, which can be done by the community, Calculation of the Break-even Point, to the calculation of the Feasibility Study.